"It's Pure Panic": The Portrayal of Residential Care in American Newspapers During COVID-19. (26th October 2020) - Allen, Laura D; Ayalon, Liat
Abstract: Background and Objectives: This study examines the discursive construction of residential care during the coronavirus disease 2019 (COVID-19) pandemic in 3 leading American newspapers: The New York Times, USA Today, and The New York Post. Research Design and Methods: A total of 54 news articles between January 21 and May 8, 2020 were identified from the LexisNexis academic database for analysis. The articles were analyzed using both a critical discourse analysis approach and a thematic analytical framework. Results: Findings indicate that residents' voices are excluded and superseded by others, namely their family members. Literary elements were used to portray residential care as shockingly dangerous, deceptive, and problematic. Blame was often assigned to an individual or group according to the political tendency of the newspaper. Discussion and Implications: A cultural model of panic and dishonesty begins to take shape through the COVID-19 pandemic. Fearmongering and the portrayal of residential care as lacking transparency will likely create future mistrust of the industry. The depiction of vulnerability and the illusion of resident inclusion in the news coverage enable paternalistic decision-making and care practices in the name of supposed protection.